Peran Cyber Public Relations dan Citra Merek Kosgoro 1957 Terhadap Advokasi Merek - Misnan, Misnan; Pranawukir, Iswahyu; Desilawati, Nur; Barizki, Rezzi Nanda (Universitas Bina Sarana Informatika, 2025)
he digital transformation has reshaped public relations practices in higher education institutions, particularly in building brand image and fostering student brand advocacy. This study aims to analyze the role of Cyber Public Relations (Cyber PR) and the brand image of KOSGORO 1957 in influencing brand advocacy among second-semester students of the Communication Studies Program at Institut Bisnis dan Informatika Kosgoro 1957 (IBI-K57). A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected using a Likert-scale questionnaire to measure students’ perceptions of Cyber PR dimensions (transparency, porosity, content richness, the internet as agent, and reach), brand image (identity, meaning, response, and resonance), and brand advocacy (recommendation, defense, engagement, and referral). Regression analysis was conducted to examine relationships among variables. Qualitative data were obtained through in-depth interviews with students and staff to enrich the understanding of how Cyber PR and brand image influence advocacy. The findings indicate that Cyber PR has a significant positive effect on brand image, while brand image strongly influences student brand advocacy. Moreover, brand image was found to mediate the relationship between Cyber PR and brand advocacy. Students highlighted that transparency, responsiveness, and relevant digital content from IBI-K57 enhanced their sense of belonging and pride in the institution. The historical foundation of KOSGORO 1957 and its values of Tri Dharma (Service, People’s Welfare, Solidarity) further reinforced emotional ties that motivated students to act as active brand advocates.In conclusion, the success of IBI-K57’s digital communication strategy relies on the synergy between effective Cyber PR practices and strong brand image management. Strategic recommendations include enhancing transparency in online communication, strengthening narratives based on KOSGORO 1957 values, and developing formal student advocacy programs to support institutional reputation sustainably.